Two new species of the genus Stericta Lederer (Lepidoptera, Pyralidae, Epipaschiinae) from Laos and Cambodia - Kim, Hanul; Lee, Tak-Gi; Cha, Yeong-Bin; Jang, Chang-Moon; Kim, Jeong-Nam; Bayarsaikhan, Ulziijargal; Bae, Yang-Seop (Zootaxa, 2023)
Two new species, Stericta jaeshini Kim & Bae, sp. nov. and S. atroaurantiaca Kim & Bae, sp. nov. are described from Southeast Asia. About 50 species of the genus Stericta have been recorded from Southeast Asia, but it has not been recorded to occur in Laos and Cambodia previously. We record the presence of this genus in these two countries for the first time in this study. Illustrations of adults and genitalia of examined species are provided. v